Improving the economic value of rice bran oil - Tiwari, G.J; Aumeeruddy, A.; Rahman, S. (Penerbit Universiti Kebangsaan Malaysia, 2014)
Cereal grains are usually considered to be sources of carbohydrate but they can also contain oil which is of considerable economic value. Rice oil is obtained from the bran produced by polishing brown rice. Key genes which control rice bran oil composition have been identified but oil quality is also affected by the rapid breakdown of the triglycerides following polishing. Several lipases in the bran have been identified by proteomic approaches. However, DNA sequence identity searches indicate that over a hundred putative lipase genes can be identified in the rice genome although it is not clear how many of these putative genes are expressed in the bran. A concerted research effort therefore is required to identify the lipases that are responsible for oil breakdown in the bran.